Tumor autophagy is associated with survival outcomes in patients with resected non-small cell lung cancer - Überall, Ivo; Gachechiladze, Mariam; Joerger, Markus; Anděl, Josef; Smičková, Petra; Kolek, Vítězslav; Grygárková, Ivona; Škarda, Josef (Lung cancer (Amsterdam, Netherlands), 2019)
OBJECTIVES: LC3A protein is associated with autophagosomes, and LC3A immunohistochemistry (IHC) is used for the detection of autophagy activity. The aim of this study was to assess the prognostic value of LC3A expression in patients with resected non-small cell lung cancer (NSCLC). MATERIALS AND METHODS: We used tissue microarrays (TMAs) constructed from 116 resected stage IB-III NSCLC patients. Standard immunohistochemistry was performed on formalin-fixed paraffin-embedded tissue sections using antibody against LC3A autophagic potein. Stained slides were scanned by Olympus dotSlide Digital Virtual Microscopy System (Japan) and the LC3A staining was evaluated digitally. Groups were compared using the Mann Whitney U test, and correlations were assessed using Spearman's rank test. Survival was calculated using Kaplan-Meier analysis. Primary study endpoint was overall survival (OS), secondardy study endpoint disease-free survival (DFS). Cut-off optimization for LC3A prognostic value was performed using the "cut-off finder' 'software (Charite, Berlin, Germany). In addition, the Kaplan Meier plotter (KmPlot) was used to assess the relationship between LC3A mRNA expression and clinical outcome (OS and DFS) in patients with NSCLC. RESULTS: From 116 patients, 88 tissue samples were available for final examination. No significant association was found between LC3A staining and other clinicopathological variables, including tumor grade, stage and histological subtype. A higher number of LC3A stone-like structures (SLSs) (>20), was significanly associated with poor OS (HR = 2.27, p = 0.011) and DFS (HR = 2.27, p = 0.003). A significant association between high LC3A mRNA and both a worse OS and worse DFS was found by KMPlot analysis in patients with stage I-III NSCLC. CONSLUSION: This retrospective study suggests that SLSs as assessed by LC3A IHC as well as LC3A mRNA expression has a clinically relevant negative prognostic value in patients with resected NSCLC, and should be further investigated.
Keywords: nádory plic; KM plotter; nemalobuněčný karcinom plic; Pneumonectomy; Lung Neoplasms; Humans; messenger RNA; analýza přežití; Carcinoma, Non-Small-Cell Lung; Biomarkers, Tumor; LC3A; Female; lidé; Overall survival; autofagie; Immunohistochemistry; Tissue Array Analysis; Survival Analysis; imunohistochemie; Cutoff finder; pneumektomie; nádorové biomarkery; Non-small cell lung cancer; RNA, Messenger; staging nádorů; ženské pohlaví; Male; prognóza; proteiny asociované s mikrotubuly; čipová analýza tkání; Disease free survival; Neoplasm Staging; Autophagy; mužské pohlaví; Prognosis; Microtubule-Associated Proteins; Stone-like structures